The mediatisation of Chinese corporate communication: A linguistic approach. (11th November 2015) - Han, Zhengrui
Abstract : The mediatisation of corporate communication transforms corporate negotiations of public companies from representative democracy to deliberative democracy, whereas the public seems to own individual access to a bountiful supply of information regarding corporate changes. However, it is unavoidable that managers become the privileged gatekeepers of media re-articulations; they orchestrate the deliberative process by selecting and construing information for public reception. Such situational complexity creates a tension in managers' engagement with the public between the need of communicative interaction informing the public and the pursuit of strategic interaction mobilising public opinion for self-interests. Drawing on previous discursive studies of the mediatisation of corporate communication (Vaara & Tienari, 2002) and the theoretical underpinnings of critical discourse analysis (Fairclough, 1992; Wodak & Meyer, 2001), this article examines how the mixing of the two types of interactions are linguistically realised in media texts produced by Chinese managers. Particular attention is paid to the strategic use of narrative structures (Labov & Waletzky, 1997), textual simplification (Bhatia, 1983, 2008), and cultural keywords (Williams, 1976/1983).